Preparation and application research of multistage enhanced SERS (Surface Enhanced Raman Scattering) composite substrate based on ZnO at Au

By preparing a ZnO@Au multi-level enhanced SERS composite substrate and a microfluidic chip, combined with the peroxidase effect of gold-mercury alloy, the sensitivity and selectivity problems of mercury ion detection in seawater were solved, and a high-sensitivity and rapid-response detection effect was achieved.

CN120778700APending Publication Date: 2025-10-14CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510929362.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

Existing technologies make it difficult to achieve high-sensitivity and high-selectivity detection of mercury ions in complex seawater media, especially in the context of high salinity and complex components. Traditional methods lack stability and are difficult to achieve accurate in-situ detection.

Method used

A ZnO@Au multi-level enhanced SERS composite substrate was used. A pyramid-shaped substrate was prepared by femtosecond laser processing and chemical etching. Combined with a microfluidic chip, indirect SERS detection was performed using the peroxidase effect of gold amalgam.

Benefits of technology

The sensitivity and selectivity of SERS detection were significantly improved, and low detection limit detection of mercury ions in seawater was achieved, with high sensitivity and rapid response characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120778700A_ABST
    Figure CN120778700A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a multistage enhanced surface enhanced Raman scattering (SERS) composite substrate based on zinc oxide (ZnO) and gold (Au), and application of the multistage enhanced SERS substrate to trace detection of mercury ions in seawater. According to the method, an inverted pyramid array structure is formed on the surface of a silicon substrate by using an anisotropic wet etching effect of potassium hydroxide (KOH) on silicon, and the inverted pyramid array structure is used as a template to prepare the pyramid array structure doped with ZnO nanoparticles. A femtosecond laser processing and ethyl lactate corrosion method is utilized to modify the surface of a substrate, a pyramid framework substrate with the surface formed by stacking ZnO nanoparticles is finally obtained, and a layer of gold film is plated on the surface of the substrate to enhance the Raman signal intensity. By utilizing the SERS chemical enhancement effect of a ZnO material and the SERS electromagnetic field enhancement effect of Au / ZnO nanoparticle gaps, the SERS signal intensity is greatly improved, the detection sensitivity of the substrate to mercury ions is enhanced, trace substances such as heavy metal ions in the ocean can be rapidly and accurately detected, and a reliable technical means is provided for marine environment monitoring.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of micro-nano sensing and SERS detection technology. Specifically, the present invention relates to the preparation of a multi-level enhanced SERS composite substrate based on ZnO@Au and its application in the detection of trace mercury ions in seawater. Background Art

[0002] Raman scattering is a light scattering phenomenon discovered by Indian physicist C.V. Raman in 1928. When monochromatic light is irradiated on a substance, most photons are ejected at the same frequency as the incident light, but the frequency of a small number of photons changes, which is called Raman scattering. Surface Enhanced Raman Scattering (SERS) is an important extension of traditional Raman scattering. It can greatly enhance the Raman signal, which is usually several orders of magnitude higher than the ordinary Raman scattering intensity. When molecules are adsorbed onto the metal surface, the Raman signal is significantly enhanced. The reason for this phenomenon is that the local electromagnetic field effect and the chemical enhancement effect on the metal surface work together to greatly enhance the interaction between the molecules and the laser light source.

[0003] Zinc oxide exhibits a significant chemical enhancement effect in the field of SERS due to its unique semiconductor properties and surface defect states. Its enhancement mechanism mainly stems from the charge transfer process caused by oxygen vacancies and lattice defects on the surface of zinc oxide. When the molecules to be measured are adsorbed on the substrate surface, localized electronic coupling is formed between the nanoparticles, and the Raman signal of the molecular vibration mode is significantly amplified through resonant charge transfer. Zinc oxide nanoparticles can form a heterojunction composite structure with precious metals (such as Au and Ag), synergizing electromagnetic field enhancement and chemical enhancement effects to significantly enhance the Raman signal. This material has the advantages of high stability, tunable optical properties and low cost, and has important application potential in trace analysis fields such as environmental pollutant detection and biomolecule recognition.

[0004] Mercury ions (Hg 2+) As a highly toxic heavy metal pollutant, it is widely distributed in water, soil and atmospheric environmental media, and has strong migration and persistent ecological risk. It is amplified along the food chain through biological enrichment, which seriously threatens the safety of aquatic ecosystems and human health. The detection of mercury ions faces multiple challenges: high salinity and complex components of seawater cause background interference, mercury ions exist in ultra-trace amounts and have various forms, coexisting heavy metals and organic ligands easily cause competitive adsorption, and traditional methods are not stable in complex media, etc., making it difficult to achieve in-situ accurate detection. SERS technology can precisely capture and identify mercury ions through the synergistic effect of specific functionalized metal nanomaterials and probe molecules. When the target molecule binds with the molecular probe modified on the surface of the noble metal nanostructure, the Raman signal of the target molecule is significantly enhanced under the effect of localized surface plasmon resonance, and the qualitative and quantitative analysis of trace mercury ions is realized through the characteristic fingerprint spectrum. The SERS detection method breaks through the technical bottleneck of heavy metal detection in complex matrix, and has ultra-high sensitivity, excellent selectivity and rapid response characteristics, providing an innovative solution for on-site detection of mercury pollution in complex systems such as environmental water and food.

[0005] Femtosecond laser processing technology, as a leading method in the field of high-precision micro-nano manufacturing, has unique technical advantages in the preparation of SERS substrates. The nonlinear multi-photon absorption effect produced by the interaction between femtosecond ultra-short pulses (10-15 seconds) and matter can realize micro, sub-micro and nano-level structure processing on the surface of metal, semiconductor and composite dielectric materials. In the preparation process of doped substrates, the high interface bonding strength of different materials leads to difficulty in corrosion separation. Based on the difference in thermal conductivity of different materials, femtosecond laser processing technology can realize non-destructive selective peeling of heterojunction interface by adjusting the thermal stress induced by laser to cause thermal expansion, thereby effectively reducing the bonding strength between materials and creating favorable conditions for subsequent separation process. SUMMARY

[0006] The purpose of the present application is to use ZnO in combination with noble metal nanoparticles to synergize the SERS chemical and physical enhancement effects, significantly improving the SERS detection sensitivity. The present application uses anisotropic chemical etching to obtain a substrate template, uses a doped solution to reverse mold, and then uses femtosecond laser modification and ethyl lactate etching to obtain a pyramid skeleton substrate with a ZnO stack on the surface. A layer of about 30 nm gold is plated using a vacuum coating instrument, and finally a pyramid-shaped SERS substrate with multi-level enhancement effect is obtained. The present application uses the peroxidase effect of gold-mercury alloy to catalyze TMB to form oxidized TMB, which has a very strong SERS signal and can be used for indirect SERS characterization of mercury ions in seawater.

[0007] To achieve the above purpose, the technical scheme provided by the present application is:

[0008] A preparation and application of a multi-level enhanced SERS composite substrate based on ZnO@Au, comprising the following steps:

[0009] Step S1, preparing a pyramid-shaped SERS substrate with multi-level enhancement effect;

[0010] A femtosecond laser was used to selectively remove the SiO2 film on the surface of a silicon wafer. The wafer was then etched in a KOH solution to obtain an inverted pyramid array. This was then molded using a PMMA-doped ZnO ethyl lactate solution to obtain a ZnO-doped pyramid array substrate. The substrate was then laser processed, ethyl lactate etched, and gold-plated to form a pyramid-shaped SERS substrate with a multi-level enhancement effect.

[0011] The step S1 is specifically as follows:

[0012] Step S11, using a femtosecond laser to remove the oxide film on the surface of the silicon wafer;

[0013] Select crystal phase <100> A silicon wafer with a 300nm SiO2 film was used as the processing material, and a femtosecond laser galvanometer processing platform was used to selectively remove the oxide film on the surface of the silicon wafer. EZCAD software was used to draw a circle array with a diameter of 50μm, and a 5μm straight line filling circle was set as the femtosecond laser processing route. The scanning spacing was set to 5μm, and the scanning speed was set to 6mm / s. The femtosecond laser output parameters were set to 1030nm central wavelength, 2.5kHz pulse repetition frequency, and 50mW laser power through the Pharos laser control module. After processing, the sample was placed in an ultrasonic cleaner for deep cleaning for more than 15 minutes, then rinsed three times with deionized water, and finally placed in a clean environment to dry naturally.

[0014] Step S12, KOH anisotropic chemical etching;

[0015] First, prepare a KOH etching solution with a concentration of 6 mol / L, measure about 10 mL of the solution and mix it with 1 mL of isopropyl alcohol and 1 mL of deionized water as the etchant for the silicon wafer. The role of isopropyl alcohol is to regulate the reaction. The silicon substrate after femtosecond laser patterning is immersed in the etching system and placed in a constant temperature magnetic stirrer for anisotropic wet etching. The total time is controlled to be 90 minutes. The silicon dioxide mask hardly reacts with KOH under this condition. The SiO2 layer in the area where the laser is not scanned effectively blocks the etching effect of the etching solution on the silicon substrate, while the exposed silicon surface in the laser scanning area reacts with the anisotropic etching solution. <100> The crystal orientation produces an inverted pyramid microstructure array dominated by the (111) crystal plane), and finally forms a periodically regularly arranged micron-scale pit array template on the surface of the silicon substrate;

[0016] Step S13, preparing a PMMA-doped ZnO pyramid-shaped substrate;

[0017] PMMA powder, zinc oxide nanoparticles, and ethyl lactate were mixed in a specific ratio. After adding a magnet, the solution was vortexed and mixed using a magnetic stirrer for at least 24 hours. The solution was then placed in a vacuum environment to remove internal bubbles, resulting in a PMMA-doped ZnO ethyl lactate solution. A certain amount of the resulting solution was poured onto a silicon template, which was then placed in a 70°C oven for at least 2 hours to cure the polymer and form a PMMA-doped ZnO pyramidal substrate.

[0018] Step S14, scanning the modified pyramid base surface with a femtosecond laser;

[0019] Based on the difference in thermal conductivity between PMMA and ZnO, laser-induced thermal stress causes thermal expansion at the interface between the two materials, effectively reducing the bonding strength between the materials and creating favorable conditions for the subsequent corrosion separation process. The laser parameters were controlled using the Pharos laser control platform, with the laser energy set to 5mW, the laser output wavelength to 1030nm, the pulse frequency to 2.5kHz, and the scan line spacing to 20μm to ensure the integrity of the surface microstructure processing. To obtain the optimal substrate processing parameters, the laser energy was adjusted to 5mW, 10mW, 15mW, and 20mW.

[0020] Step S15, etching the substrate with ethyl lactate to remove PMMA on the surface;

[0021] Ethyl lactate and isopropyl alcohol were mixed in a certain ratio to obtain an etching solution. The laser-processed substrate was picked up with tweezers and immersed in the etching solution for 5 seconds. After the etching was completed, the substrate was immediately immersed in deionized water to wash away the ethyl lactate and terminate the etching, resulting in a pyramid skeleton substrate with stacked ZnO nanoparticles on the surface. To optimize the processing parameters, the ethyl lactate etching time was adjusted to 5 seconds, 10 seconds, 15 seconds, and 20 seconds.

[0022] Step S16, gold plating the substrate surface;

[0023] Place the sample platform with the substrate sample upside down in the vacuum coating instrument and turn on the vacuum pump until the vacuum degree of the chamber reaches 5×10 -4 When the pressure is below Pa, open the crucible baffle, turn on the main power of the electronic cabinet, turn on the filament to preheat for two minutes, adjust the light spot to the center of the target, wait for the beam to stabilize at the set value, open the sample baffle, and place the beam on the substrate surface. The gold film was evaporated at a high rate. When the film thickness reached about 30 nm, the evaporation was terminated, the electron beam source was turned off, and the chamber pressure was released, ultimately obtaining a pyramid-shaped SERS substrate with a multi-level enhancement effect.

[0024] Step S2, preparation of microfluidic chip;

[0025] Spin-coat photoresist onto a clean silicon wafer, place the mask and wafer in a UV lithography machine for exposure, and transfer the pattern on the mask to the silicon wafer through photoresist curing. PDMS is then poured into the silicon template, and after curing, cutting, and sealing, a microfluidic chip is obtained.

[0026] The step S2 is specifically as follows:

[0027] Step S21, chip template preparation;

[0028] The silicon wafer is cleaned with isopropyl alcohol, dried with nitrogen, and then heated on a 100°C hot plate for more than 10 minutes to remove residual solvent and enhance the adhesion of the photoresist. The photoresist is dropped onto the center of the silicon wafer and spin-coated at a set speed using a spunbond to form a uniform film. The silicon wafer is then placed on a 95°C hot plate and heated for more than 15 minutes to remove the solvent and enhance the stability of the photoresist. The mask is aligned with the coated silicon wafer and exposed under a UV photolithography machine. After that, the uncured photoresist is removed by gently shaking and soaking in ethyl lactate developer for about 10 minutes to form the channel structure of the microfluidic chip.

[0029] Step S22, preparing a PDMS microfluidic chip;

[0030] Mix the PDMS prepolymer and curing agent in a certain mass ratio, stir and vacuum degas for more than 30 minutes to remove bubbles, pour the PDMS mixture into the chip mold obtained by photolithography, let it stand for 2 minutes, and then place it in a 70°C oven to cure for more than 120 minutes to obtain a PDMS chip. An iron block needs to be placed at the base position in the chip to reserve reaction space. Use a scalpel to peel off the cured PDMS block, and use a punch to open holes at the inlet and outlet of the channel as liquid inlet and outlet channels. Next, the PDMS chip and the glass slide are simultaneously treated with oxygen plasma for 90 seconds to produce hydroxyl groups on their surface to facilitate close fitting. Immediately after treatment, the PDMS chip and the glass slide are bonded together (the substrate is placed in the chip in advance) to complete the sealing. SERS detection of mercury ions can then be performed in the microfluidic chip;

[0031] Step S3, SERS detection of mercury ions on the microfluidic chip;

[0032] Prepare the mercury ion detection solution, pass the detection solution and the standard solution containing mercury ions into the microfluidic channel together, and use a Raman spectrometer to perform Raman characterization after incubation in the channel;

[0033] The step S3 is specifically as follows:

[0034] Step S31, TMB oxidation reaction;

[0035] A 0.5M TMB solution, a 5% hydrogen peroxide solution, deionized water, and gold nanoparticle sol were mixed to obtain a 600μL mercury ion detection solution. 90μL of the detection solution and 10μL of the mercury ion-containing test solution were introduced into the microfluidic chip from two channels, respectively, and incubated for about 15 minutes. The gold-mercury alloy formed by the combination of mercury ions and gold nanoparticles has strong peroxidase activity, which catalyzes the reaction of hydrogen peroxide with TMB to generate oxidized TMB. Oxidized TMB is detected at 1604cm -1 There is a strong Raman peak at the center, and the intensity of the Raman peak can be used to reflect the concentration of mercury ions;

[0036] Step S32, mercury ion detection;

[0037] After the reaction was complete, the microfluidic chip was placed on the sample stage of a Renishaw Raman spectrometer. A 633nm laser light source was turned on, and a 50x objective lens was selected. The focus was adjusted to the SERS substrate, with laser power set to 5%, a single signal acquisition time of 3 seconds, and a single signal acquisition cycle. Five random locations on each substrate were tested and the averaged data was used as the final data.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] 1. A new type of SERS composite substrate was designed, which uses the electron transfer property of zinc oxide to achieve SERS chemical enhancement, and uses the tiny gaps between nanoparticles combined with gold plating to achieve SERS physical enhancement. The synergistic enhancement effect coupling makes the SERS substrate have higher detection sensitivity.

[0040] 2. An integrated microfluidic SERS sensor was designed. The SERS substrate was embedded in the microfluidic chip, and TMB was used for indirect SERS-colorimetric dual-modal detection of mercury ions, which could achieve a lower detection limit. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 This is a flow chart for preparing the SERS substrate of the present invention;

[0042] Figure 2 This is a physical picture of the multi-level enhanced SERS substrate of the present invention;

[0043] Figure 3 This is a concentration gradient diagram of the SERS substrate of the present invention detecting Raman reporter molecules (malachite green isothiocyanate, MGITC);

[0044] Figure 4 This is a uniformity test diagram of the SERS substrate of the present invention based on MGITC detection;

[0045] Figure 5 is the SERS response intensity of different material substrates to MGITC;

[0046] Figure 6 This is the concentration gradient diagram of mercury ion detection by SERS sensor;

[0047] Figure 7 This is the specific detection diagram of SERS sensor for mercury ions. DETAILED DESCRIPTION

[0048] The technical solutions in the embodiments of the present application will be described clearly and completely below with reference to the accompanying drawings.

[0049] The purpose of the present invention is to utilize ZnO in combination with noble metal nanoparticles to synergize the SERS chemical and physical enhancement effects, significantly improving the SERS detection sensitivity. The present invention utilizes anisotropic chemical etching to obtain a substrate template. After using a doping solution to cast the mold, a two-step process of femtosecond laser modification and ethyl lactate etching is performed to obtain a pyramidal skeleton substrate with a surface stacked with ZnO. A 30nm layer of gold is then plated using a vacuum coating apparatus to ultimately obtain a pyramidal SERS substrate with a multi-level enhancement effect. The present invention utilizes the peroxidase effect of gold-mercury alloy to catalyze TMB to form oxidized TMB. Oxidized TMB has an extremely strong SERS signal and can be used for indirect SERS characterization of mercury ions in seawater.

[0050] To achieve the above object, the technical solution provided by the present invention is:

[0051] A preparation and application of a multi-level enhanced SERS composite substrate based on ZnO@Au, comprising the following steps:

[0052] Step S1, preparing a pyramid-shaped SERS substrate with multi-level enhancement effect;

[0053] A femtosecond laser was used to selectively remove the SiO2 film on the surface of a silicon wafer. The wafer was then etched in a KOH solution to obtain an inverted pyramid array. This was then molded using a PMMA-doped ZnO ethyl lactate solution to obtain a ZnO-doped pyramid array substrate. The substrate was then laser processed, ethyl lactate etched, and gold-plated to form a pyramid-shaped SERS substrate with a multi-level enhancement effect.

[0054] The step S1 is specifically as follows:

[0055] Step S11, using a femtosecond laser to remove the oxide film on the surface of the silicon wafer;

[0056] Select crystal phase <100> A silicon wafer with a 300nm SiO2 film was used as the processing material, and a femtosecond laser galvanometer processing platform was used to selectively remove the oxide film on the surface of the silicon wafer. EZCAD software was used to draw a circle array with a diameter of 50μm, and a 5μm straight line filling circle was set as the femtosecond laser processing route. The scanning spacing was set to 5μm, and the scanning speed was set to 6mm / s. The femtosecond laser output parameters were set to 1030nm central wavelength, 2.5kHz pulse repetition frequency, and 50mW laser power through the Pharos laser control module. After processing, the sample was placed in an ultrasonic cleaner for deep cleaning for more than 15 minutes, then rinsed three times with deionized water, and finally placed in a clean environment to dry naturally.

[0057] Step S12, KOH anisotropic chemical etching;

[0058] First, prepare a KOH etching solution with a concentration of 6 mol / L, measure about 10 mL of the solution and mix it with 1 mL of isopropyl alcohol and 1 mL of deionized water as the etching solution for the silicon wafer. The role of isopropyl alcohol is to regulate the reaction. The silicon substrate after femtosecond laser patterning is immersed in the etching system and placed in a constant temperature magnetic stirrer for anisotropic wet etching. The total time is controlled to be 90 minutes. The silicon dioxide mask hardly reacts with KOH under this condition. The SiO2 layer in the area where the laser is not scanned effectively blocks the etching effect of the etching solution on the silicon substrate, while the exposed silicon surface in the laser scanning area reacts with the anisotropic etchant. <100> The crystal orientation produces an inverted pyramid microstructure array dominated by the (111) crystal plane, and ultimately forms a periodically regularly arranged micron-scale pit array template on the surface of the silicon substrate;

[0059] Step S13, preparing a PMMA-doped ZnO pyramid-shaped substrate;

[0060] PMMA powder, zinc oxide nanoparticles, and ethyl lactate were mixed in a specific ratio. After adding a magnet, the solution was swirled and mixed for at least 24 seconds using a magnetic stirrer. The solution was then placed in a vacuum environment to remove internal bubbles, resulting in a PMMA-doped ZnO ethyl lactate solution. A certain amount of the resulting solution was poured onto a silicon template, which was then placed in a 70°C oven for at least 2 hours to cure the polymer and form a PMMA-doped ZnO pyramidal substrate.

[0061] Step S14, scanning the modified pyramid base surface with a femtosecond laser;

[0062] Based on the difference in thermal conductivity between PMMA and ZnO, laser-induced thermal stress causes thermal expansion at the interface between the two materials, effectively reducing the bonding strength between the materials and creating favorable conditions for the subsequent corrosion separation process. The laser parameters were controlled using the Pharos laser control platform, with the laser energy set to 5mW, the laser output wavelength to 1030nm, the pulse frequency to 2.5kHz, and the scan line spacing to 20μm to ensure the integrity of the surface microstructure processing. To obtain the optimal substrate processing parameters, the laser energy was adjusted to 5mW, 10mW, 15mW, and 20mW.

[0063] Step S15, etching the substrate with ethyl lactate to remove PMMA on the surface;

[0064] Ethyl lactate and isopropyl alcohol were mixed in a certain ratio to obtain an etching solution. The laser-processed substrate was picked up with tweezers and immersed in the etching solution for 5 seconds. After the etching was completed, the substrate was immediately immersed in deionized water to wash away the ethyl lactate and terminate the etching, resulting in a pyramid skeleton substrate with stacked ZnO nanoparticles on the surface. To optimize the processing parameters, the ethyl lactate etching time was adjusted to 5 seconds, 10 seconds, 15 seconds, and 20 seconds.

[0065] Step S16, gold plating the substrate surface;

[0066] Place the sample platform with the substrate sample upside down in the vacuum coating instrument and turn on the vacuum pump until the vacuum degree of the chamber reaches 5×10 -4 When the pressure is below Pa, open the crucible baffle, turn on the main power of the electronic cabinet, turn on the filament to preheat for two minutes, adjust the light spot to the center of the target, wait for the beam to stabilize at the set value, open the sample baffle, and place the beam on the substrate surface. The gold film was evaporated at a high rate. When the film thickness reached about 30 nm, the evaporation was terminated, the electron beam source was turned off, and the chamber pressure was released, ultimately obtaining a pyramid-shaped SERS substrate with a multi-level enhancement effect.

[0067] The substrate preparation flow chart is as follows Figure 1 As shown, Figure 2 This is the base physical picture. Figure 2 The size of a single pyramid in A is about 70×60×40μm. Figure 2 B shows the nanoscale stacking structure produced by gold plating of ZnO particles on the substrate surface; Figure 3 、 4 , 5 are substrate SERS performance tests, Figure 3 The detection limit of the substrate for MGITC (a Raman reporter molecule) is 10 -10 The M level indicates that the substrate has a high detection sensitivity. Figure 4 For a uniform waterfall chart, select 10 -6MGITC was used as a reporter molecule to test 16 spectra at different positions, proving that the substrate had good uniformity. Figure 5 Still using 10 -6 The MMGITC target was used to verify the SERS response of different material substrates to the same concentration of reporter molecules, proving that the ZnO@Au substrate has a better SERS enhancement effect than other substrates.

[0068] Step S2, preparation of microfluidic chip;

[0069] Spin-coat photoresist onto a clean silicon wafer, place the mask and wafer in a UV lithography machine for exposure, and transfer the pattern on the mask to the silicon wafer through photoresist curing. PDMS is then poured into the silicon template, and after curing, cutting, and sealing, a microfluidic chip is obtained.

[0070] The step S2 is specifically as follows:

[0071] Step S21, chip template preparation;

[0072] The silicon wafer was cleaned with isopropyl alcohol, dried with nitrogen, and then heated on a 100°C hot plate for more than 10 minutes to remove residual solvent and enhance the adhesion of the photoresist. The photoresist was dropped onto the center of the silicon wafer and spin-coated at a set speed using a spunbond to form a uniform film. The silicon wafer was then placed on a 95°C hot plate and heated for more than 15 minutes to remove the solvent and enhance the stability of the photoresist. The mask was aligned with the coated silicon wafer and exposed under a UV photolithography machine. Uncured photoresist was then removed by gently shaking and soaking in ethyl lactate developer for 10 minutes to form the channel structure of the microfluidic chip.

[0073] Step S22, preparing a PDMS microfluidic chip;

[0074] Mix the PDMS prepolymer and curing agent in a mass ratio of 15:1, stir and vacuum degas for more than 30 minutes to remove bubbles, pour the PDMS mixture into the chip mold obtained by photolithography, let it stand for 2 minutes, and then place it in a 70°C oven to cure for more than 120 minutes to obtain a PDMS chip. An iron block needs to be placed at the base position in the chip to reserve reaction space. Use a scalpel to peel off the cured PDMS block, and use a punch to open holes at the inlet and outlet of the channel as liquid inlet and outlet channels. Next, the PDMS chip and the glass slide are simultaneously treated with oxygen plasma for 90 seconds to produce hydroxyl groups on their surface to facilitate close fitting. Immediately after treatment, the PDMS chip and the glass slide are bonded together (the substrate is placed in the chip in advance) to complete the sealing. SERS detection of mercury ions can then be performed in the microfluidic chip;

[0075] Step S3, SERS detection of mercury ions on the microfluidic chip;

[0076] Prepare the mercury ion detection solution, pass the detection solution and the standard solution containing mercury ions into the microfluidic channel together, and use a Raman spectrometer to perform Raman characterization after incubation in the channel;

[0077] The step S3 is specifically as follows:

[0078] Step S31, TMB oxidation reaction;

[0079] A 0.5M TMB solution, a 5% hydrogen peroxide solution, deionized water, and gold nanoparticle sol were mixed to obtain a 600μL mercury ion detection solution. 90μL of the detection solution and 10μL of the mercury ion-containing test solution were introduced into the microfluidic chip from two channels, respectively, and incubated for about 15 minutes. The gold-mercury alloy formed by the combination of mercury ions and gold nanoparticles has strong peroxidase activity, which catalyzes the reaction of hydrogen peroxide with TMB to generate oxidized TMB. Oxidized TMB is detected at 1604cm -1 There is a strong Raman peak at the center, and the intensity of the Raman peak can be used to reflect the concentration of mercury ions;

[0080] Step S32, mercury ion detection;

[0081] After the reaction was complete, the microfluidic chip was placed on the sample stage of a Renishaw Raman spectrometer. A 633nm laser light source was turned on, and a 50x objective lens was selected. The focus was adjusted to the SERS substrate, with laser power set to 5%, a single signal acquisition time of 3 seconds, and a single signal acquisition cycle. Five random locations on each substrate were tested and the averaged data was used as the final data.

[0082] Figure 6 The Raman spectra of oxidized TMB as the reporter molecule at different mercury ion concentrations are shown in the wavelength range of 1604 cm -1 The peak at 10 is used as the characteristic peak, and the detection limit of mercury ions can reach 10 -11 M, Figure 7 The Raman characteristic peak intensities of different ions added to the reaction system are shown, indicating that the detection scheme has strong specificity.

[0083] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A method for preparing a multi-level enhanced SERS substrate based on ZnO@Au, characterized in that: The following steps are included: Step S1, preparing a pyramid-shaped SERS substrate with multi-level enhancement effect; A femtosecond laser was used to selectively remove the silicon dioxide (SiO2) film on the surface of a silicon wafer. The wafer was then etched in a KOH solution to obtain an inverted pyramid array. This was then molded with a PMMA-doped ZnO solution to obtain a ZnO-doped pyramid array substrate. The substrate was then laser processed, etched with ethyl lactate, and gold-plated to obtain a pyramid-shaped SERS substrate with a multi-level enhancement effect. Step S3, SERS detection of mercury ions on the microfluidic chip; Prepare the mercury ion detection solution, and introduce the detection solution and the standard solution containing mercury ions into the microfluidic channel. After incubation in the channel, Raman characterization is performed using a Raman spectrometer.

2. The method for preparing a multi-level enhanced SERS composite substrate based on ZnO@Au according to claim 1, characterized in that: The step S1 is specifically as follows: Step S11, using a femtosecond laser to remove the oxide film on the surface of the silicon wafer; Select crystal phase <100> A silicon wafer with a 300nm SiO2 film was used as the processing material, and a femtosecond laser galvanometer processing platform was used to selectively remove the oxide film on the surface of the silicon wafer. EZCAD software was used to draw a circle array with a diameter of 50μm, and a 5μm straight line filling circle was set as the femtosecond laser processing route. The scanning spacing was set to 5μm, and the scanning speed was set to 6mm / s. The femtosecond laser output parameters were set to 1030nm central wavelength, 2.5kHz pulse repetition frequency, and 50mW laser power through the Pharos laser control module. After processing, the sample was placed in an ultrasonic cleaner for deep cleaning for more than 15 minutes, then rinsed three times with deionized water, and finally placed in a clean environment to dry naturally. Step S12, KOH anisotropic chemical etching; First, prepare a KOH etching solution with a concentration of 6 mol / L, measure about 10 mL of the solution and mix it with 1 mL of isopropyl alcohol and 1 mL of deionized water as the etchant for the silicon wafer. The role of isopropyl alcohol is to regulate the reaction. The silicon substrate after femtosecond laser patterning is immersed in the etching system and placed in a constant temperature magnetic stirrer for anisotropic wet etching. The total time is controlled to be 90 minutes. The silicon dioxide mask hardly reacts with KOH under this condition. The SiO2 layer in the area where the laser is not scanned effectively blocks the etching effect of the etching solution on the silicon substrate, while the exposed silicon surface in the laser scanning area reacts with the anisotropic etchant. <100> The crystal orientation produces an inverted pyramid microstructure array dominated by the (111) crystal plane, and ultimately forms a periodically regularly arranged micron-scale pit array template on the surface of the silicon substrate; Step S13, preparing a polymethyl methacrylate (PMMA)-doped ZnO pyramid-shaped substrate; PMMA powder, zinc oxide nanoparticles, and ethyl lactate were mixed in a specific ratio. After adding a magnet, the solution was vortexed and mixed using a magnetic stirrer for at least 24 hours. The solution was then placed in a vacuum environment to remove internal bubbles, resulting in a PMMA-doped ZnO ethyl lactate solution. A certain amount of the resulting solution was poured onto a silicon template, which was then placed in a 70°C oven for at least 2 hours to cure the polymer and form a PMMA-doped ZnO pyramidal substrate. Step S14, scanning the modified pyramid base surface with a femtosecond laser; Based on the difference in thermal conductivity between PMMA and ZnO, laser-induced thermal stress causes thermal expansion at the interface between the two materials, effectively reducing the bonding strength between the materials and creating favorable conditions for the subsequent corrosion separation process. The laser parameters were controlled using the Pharos laser control platform, with the laser energy set to 5mW, the laser output wavelength to 1030nm, the pulse frequency to 2.5kHz, and the scan line spacing to 20μm to ensure the integrity of the surface microstructure processing. To obtain the optimal substrate processing parameters, the laser energy was adjusted to 5mW, 10mW, 15mW, and 20mW. Step S15, etching the substrate with ethyl lactate to remove PMMA on the surface; Ethyl lactate and isopropyl alcohol were mixed in a certain proportion to obtain an etching solution. The laser-processed substrate was picked up with tweezers and immersed in the etching solution for 5 seconds. After the etching was completed, the substrate was immediately immersed in deionized water to wash away the ethyl lactate and terminate the etching, obtaining a pyramid skeleton substrate with stacked ZnO nanoparticles on the surface. In order to optimize the processing parameters, the ethyl lactate etching time was adjusted to 5 seconds, 10 seconds, 15 seconds, and 20 seconds.

3. The method for preparing a multi-level enhanced SERS composite substrate based on ZnO@Au according to claim 1, characterized in that: The step S3 is specifically as follows: Step S31, TMB oxidation reaction; A 0.5M TMB solution, a 5% hydrogen peroxide solution, deionized water, and gold nanoparticle sol were mixed to obtain a 600μL mercury ion detection solution. 90μL of the detection solution and 10μL of the mercury ion-containing test solution were introduced into the microfluidic chip from two channels, respectively, and incubated for about 15 minutes. The gold-mercury alloy formed by the combination of mercury ions and gold nanoparticles has strong peroxidase activity, which catalyzes the reaction of hydrogen peroxide with TMB to generate oxidized TMB. Oxidized TMB is detected at 1604cm -1 There is a strong Raman peak at the center, and the intensity of the Raman peak can be used to reflect the concentration of mercury ions; Step S32, mercury ion detection; After the reaction was complete, the microfluidic chip was placed on the sample stage of a Renishaw Raman spectrometer. A 633nm laser light source was activated, and a 50x objective lens was selected. The focus was adjusted to the SERS substrate. The laser power was set to 5%, the single signal acquisition time was 3 seconds, and the signal acquisition was repeated once. Five random locations on each substrate were tested, and the average spectrum was used as the final data.

4. The method for preparing a laser-induced plasma SERS substrate according to claim 1, wherein: In the multi-level enhanced substrate prepared in step S1, the ZnO particle size is 100 nm, the Au film thickness is about 30 nm, and the synergistic effect of ZnO and Au enables the substrate to have a good SERS enhancement effect.

5. A method for preparing a multi-stage enhanced SERS composite substrate based on ZnO@Au as claimed in any one of claims 1 to 3 and its application in detecting mercury ions in seawater using a SERS microfluidic sensor.